Efficacy and safety of bipolar androgen therapy in castration-resistant prostate cancer following abiraterone or enzalutamide resistance: A systematic review - You, Xiangyun; Huang, Shan; Wang, Xin’an; Yi, Cheng; Gong, Niandong; Yu, Junfeng; Xu, Chengdang; Xiang, Zhendong (Frontiers in Endocrinology, 2023)
Bipolar androgen therapy (BAT) is a new endocrinologic treatment for castration-resistant prostate cancer (CRPC) that can restore some patients’ sensitivity to drugs such as abiraterone (Abi) and enzalutamide (Enz).We performed a meta-analysis using STATA16. Sensitivity analyses were performed by examining the effects of individual studies using different effect models and detecting any publication bias using the Harbord test.In a total of 107 unique records, ten studies were included in the final meta-analysis. Participants who underwent BAT achieved a PSA50 response rate of 27% (95%CI [0.22,0.31], I2=17.98%), ORR of 34% (95%CI [0.24,0.43], I2=0), and incidence of AEs (grade≥3) of 14% (95%CI [0.09,0.19], I2=0). Patients who completed BAT proceeded to AR-targeted therapy (Abi or Enz) and achieved a PSA50 response rate of 67% (95% CI [0.61,0.74 ], I2=0). Based on our multiple subgroup analysis, patients with prior Enz resistance had a stronger impact on the PSA50 of AR-target therapy rechallenge.The results of this meta-analysis indicate that BAT is a safe and effective treatment for patients who have progressed after Abi or Enz. BAT can trigger the resensitization of patients with CRPC to subsequent endocrine therapy and improve the overall survival of patients and their quality of life.